Incident spectral solar irradiance measured above sea ice at station PS122/2_25-104 on 2020-02-22, survey 1, version 2.0 - Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller; Marcel Nicolaus (PANGAEA, 2025)
Incident solar irradiance was measured using an ACC (Advanced-Cosine-Collector) RAMSES hyper-spectral radiometer (TriOS) installed on the sea ice during the MOSAiC expedition between November 2019 and September 2020. All times are given in Universal Coordinated Time (UTC).
In: Anhaus, P et al. (2025): Spectral solar radiation over and under sea ice during the MOSAiC expedition 2019/20, version 2.0 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979856